Peruvian household dietary diversity in children between 6 to 35 months - Tarqui Mamani, Carolina (2016)
Introduction. Household dietary diversity is key element in the quality of the diet in children. Objective. To estimate household dietary diversity and chronic malnutrition (CM) in Peruvian children. Design. A cross-sectional study was conducted during 2012-2013. Setting. National Institute of Health, Lima, Peru. Participants. Children between 6 to 35 months living in Peruvian households. Interventions. Probabilistic, stratified and multistage sampling. The sample included 13 216 households with 1 315 children. Dietary diversity (DD) was defined as 4-7 intake of food groups during the previous day by the World Health Organization (WHO) standard. An analysis of complex samples was made in SPSS and the weighting factor was adjusted. Percentages, chi square and OR were calculated. Written informed consent of the parents was requested. Main outcome measures. Dietary diversity. Results. 75.5% of children received from 4 to more food groups. Children (78.5%) had higher frequency of DD than girls (72.5%). Children living in urban areas had increased DD. Poor children had high DD (80.2%). Meat consumption was fourth in the order of most foods consumed by children. The DD was associated with the DC (p> 0.05). Age 6-11 was protective factor of DC. The girls, rural areas, children living in the mountains, jungle, the primary education level, poverty were associated with DC. Conclusions. Three quarters of Peruvian children age 6-35 months had adequate household dietary diversity. The DD was associated with CM although the association was not significant.